The Influence of School Infrastructure and Teacher Competencies on Student Competencies in Conducting Field Work Practices in Schools SMK Swasta Teladan Rampah - Reni Widya Prasela Simatupang (Outline Publisher, 2022)
This study aims to determine the effect of school infrastructure and teacher competence on student competence in carrying out field work practices at the Medan Teladan Private Vocational School. This research was conducted at the Medan Teladan Private Vocational School on Jln. Medan No. 5 Sei Rampah, Sei Rampah Subdistrict, Serdang Bedagai Regency, North Sumatra Province where the population in this study was 102 students and a sample of 50 students. The technique of collecting data in this research is through observation and distributing questionnaires. In the test of the validity of the analysis of the questionnaire items using the Product Moment correlation formula, the reliability test was carried out using Cronbach alpha. Data processing is carried out using the SPSS 25.0 application. The results of the study can be concluded that there is a positive and significant effect between school infrastructure and student competence in conducting fieldwork practices, furthermore, there is a positive and significant influence between teacher competence and student competence in conducting fieldwork practices, and there is a positive and significant influence between facilities and infrastructure. school infrastructure and teacher competence on student competence in conducting fieldwork practices.